The roles of Pleurotus ostreatus HAUCC 162 laccase isoenzymes in decolorization of synthetic dyes and the transformation pathways. (November 2019) - Zhuo, Rui; Zhang, Jingwen; Yu, Hongbo; Ma, Fuying; Zhang, Xiaoyu
Abstract: Fungal laccases have shown great potential in industrial and environmental applications. They are generally produced as laccase isoenzymes. Thus, to further study the properties of different laccase isoenzymes and their performance in bio-remediation is essential for a deep understanding of laccase function and application. In this study, three Pleurotus ostreatus HAUCC 162 laccase isoenzymes were heterologously expressed, and the effects of different inhibitors, metal ions, and organic solvents on the activity of recombinant laccases were evaluated. In the dye decolorization test, LACC6 showed the highest ability to remove Malachite green (MG), Remazol Brilliant Blue R (RBBR), Bromophenol blue (BB), and Methyl orange (MO) among the three recombinant laccases. Removal rates within 24 h were 91.5%, 84.9%, 79.1%, and 73.1% for MG (100 mg/L), RBBR (100 mg/L), BB (100 mg/L), and MO (100 mg/L), respectively. The MG and RBBR transformation pathways were proposed by using High Performance Liquid Chromatography-Mass Spectrometry (LC–MS) analysis. Based on the results of this work, the production of recombinant LACC6 or improving the portion of LACC6 in the crude extracellular laccase may advance synthetic dye removal. Graphical abstract: Image 10788 Highlights: Three Pleurotus ostreatus HAUCC 162 laccase isoenzymes were heterologously expressed. Effect of inhibitors, metal ions and organic solvents on laccases were evaluated. Recombinant LACC6 showed higher decolorization efficiency than LACC9 and LACC10. Transformation pathways of MG and RBBR were analyzed using LC-MS.